Strategi Pemasaran Restoran Sunan Drajat dalam Meningkatkan Pendapatan Usaha Mikro, Kecil, dan Menengah (UMKM) - Juliyani, Erly; Abidah, Zakiyatul (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
This study in-depth analyzes the marketing strategies implemented by Sunan Drajat Restaurant, a Micro, Small, and Medium Enterprises (MSMEs), in an effort to increase revenue in the midst of increasingly fierce business competition. In this digital era, an effective marketing strategy is a determining factor for the success of MSMEs. This study uses a qualitative descriptive approach, which involves data collection through direct observation, in-depth interviews with restaurant owners and customers, and documentation analysis related to marketing activities carried out. The results of the study show that Sunan Drajat Restaurant adopts a variety of innovative marketing strategies. One of the key strategies is the utilization of digital marketing through social media, which allows restaurants to reach a wider audience and build interactions with customers. In addition, the restaurant also establishes strategic cooperation with local business partners, such as raw material providers and delivery services, to expand market reach. Improving the quality of services and products, including menu innovation and improving restaurant facilities, is also a key focus in marketing strategies. The implementation of these strategies has proven to be effective in significantly increasing the number of customers and restaurant revenue. This research provides valuable insights for other MSME players in developing adaptive and innovative marketing strategies, in order to increase competitiveness and ensure the sustainability of their business in a competitive market